ANALISIS HUBUNGAN ANTARA MEDIA PEMBELAJARAN DIGITAL DAN CETAK DENGAN KEMAMPUAN MEMBACA (MAHARAH QIRO’AH) SISWA MA MIFTAHUSH SHIBYAN MALANG - Muhammad Fahmi Azizi; M. Abdul Hamid; Nur Qomari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the relationship between the use of digital learning media and printed learning media and students’ reading skills (maharah qira’ah) at Madrasah Aliyah Miftahush Shibyan Malang. The purpose of this study is to determine whether there is a relationship, as well as the strength of the relationship, between these two types of learning media and students’ reading ability. The method used is a quantitative approach with a correlational research design. Data were collected through a reading skills test and a questionnaire on the use of learning media, which were then analyzed using the Spearman Rank correlation test due to the data not being normally distributed. The results of the study indicate a positive and significant relationship between digital learning media and students’ reading skills, as evidenced by a correlation coefficient of 0.684. In addition, a positive and significant relationship was also found between print-based learning media and students’ reading skills, with a correlation coefficient of 0.713. These findings suggest that both types of learning media have a strong association with reading skills, with print media demonstrating a slightly higher level of correlation compared to digital media. Based on these results, the null hypothesis (H₀), which states that there is no relationship between learning media and students’ reading skills, is rejected, while the alternative hypothesis (H₁), which posits that such a relationship exists, is accepted. Therefore, it can be concluded that the use of both digital and print learning media contributes significantly to the improvement of students’ reading skills.